Anti‐tumor activity of the ATR inhibitor AZD6738 in HER2 positive breast cancer cells. Issue 1 (21st October 2016) - Kim, Hee‐Jun; Min, Ahrum; Im, Seock‐Ah; Jang, Hyemin; Lee, Kyung Hun; Lau, Alan; Lee, Miso; Kim, Seongyeong; Yang, Yaewon; Kim, Jungeun; Kim, Tae Yong; Oh, Do‐Youn; et al.
Abstract : Ataxia telangiectasia and Rad3‐related (ATR) proteins are sensors of DNA damage, which induces homologous recombination (HR)‐dependent repair. ATR is a master regulator of DNA damage repair (DDR), signaling to control DNA replication, DNA repair and apoptosis. Therefore, the ATR pathway might be an attractive target for developing new drugs. This study was designed to investigate the antitumor effects of the ATR inhibitor, AZD6738 and its underlying mechanism in human breast cancer cells. Growth inhibitory effects of AZD6738 against human breast cancer cell lines were studied using a 3‐(4, 5‐dimethylthiazol‐2‐yl)−2, 5‐diphenyltetrazolium bromide (methyl thiazolyl tetrazolium, MTT) assay. Cell cycle analysis, Western blotting, immunofluorescence and comet assays were also performed to elucidate underlying mechanisms of AZD6738 action. Anti‐proliferative and DDR inhibitory effects of AZD6738 were demonstrated in human breast cancer cell lines. Among 13 cell lines, the IC50 values of nine cell lines were less than 1 μmol/L using MTT assay. Two cell lines, SK‐BR‐3 and BT‐474, were chosen for further evaluation focused on human epidermal growth factor receptor 2 (HER2)‐positive breast cancer cells. Sensitive SK‐BR‐3 but not the less sensitive BT‐474 breast cancer cells showed increased level of apoptosis and S phase arrest and reduced expression levels of phosphorylated check‐point kinase 1 (CHK1) and other repair markers. Decreased functional CHK1 expression induced DNA damage accumulation due to HR inactivation. AZD6738 showed synergistic activity with cisplatin. Understanding the antitumor activity and mechanisms of AZD6738 in HER2‐positive breast cancer cells creates the possibility for future clinical trials targeting DDR in HER2‐positive breast cancer treatment. Abstract : What's new? Inhibitors of the DNA damage repair (DDR) pathway have emerged as new therapeutics in breast and ovarian cancers. Here the authors uncover anti‐proliferative and DDR‐inhibitory activities of an inhibitor of the ataxia telangiectasia and Rad3‐related (ATR) proteins, AZD6738, in human breast cancer cell lines, especially those positive for the human epidermal growth factor receptor 2 (HER2). As ATR is a master regulator of DDR, this study underscores the relevance of DDR as a new therapeutic target in HER2‐positive breast cancer.